Cultivation of Human Microvascular Endothelial Cells on Topographical Substrates to Mimic the Human Corneal Endothelium - Jie Shi Chua; Li Xiang Liew; Evelyn K.F. Yim (Journal of Functional Biomaterials, 2013)
Human corneal endothelial cells have a limited ability to replicate in vivo and in vitro. Allograft transplantation becomes necessary when an accident or trauma results in excessive cell loss. The reconstruction of the cornea endothelium using autologous cell sources is a promising alternative option for therapeutic or in vitro drug testing applications. The native corneal endothelium rests on the Descemet’s membrane, which has nanotopographies of fibers and pores. The use of synthetic topographies mimics the native environment, and it is hypothesized that this can direct the behavior and growth of human microvascular endothelial cells (HMVECs) to resemble the corneal endothelium. In this study, HMVECs are cultivated on substrates with micron and nano-scaled pillar and well topographies. Closely packed HMVEC monolayers with polygonal cells and well-developed tight junctions were formed on the topographical substrates. Sodium/potassium (Na+/K+) adenine triphosphatase (ATPase) expression was enhanced on the microwells substrate, which also promotes microvilli formation, while more hexagonal-like cells are found on the micropillars samples. The data obtained suggests that the use of optimized surface patterning, in particular, the microtopographies, can induce HMVECs to adopt a more corneal endothelium-like morphology with similar barrier and pump functions. The mechanism involved in cell contact guidance by the specific topographical features will be of interest for future studies.